Size-dependent shape and tilt transitions in In2O3 nanoislands grown on cubic Y-stabilized ZrO2(001) by molecular beam epitaxy. - Zhang, K; Bourlange, A; Egdell, R; Collins, S; Bean, R; Robinson, I; Cowley, R (2012)
The growth of In(2)O(3) on cubic Y-stabilized ZrO(2)(001) by molecular beam epitaxy leads to formation of nanoscale islands which may tilt relative to the substrate in order to help accommodate the 1.7% tensile mismatch between the epilayer and the substrate. High-resolution synchrotron-based X-ray diffraction has been used in combination with atomic force microscopy to probe the evolution in island morphology, orientation, and tilt with island size. Very small islands formed at low substrate coverage are highly strained but exhibit no tilt, while intermediate islands are tilted randomly in all directions, giving rise to distinctive doughnut-shaped structure in three-dimensional reciprocal space isosurfaces. The largest islands with lateral sizes on the order of 1 μm tilt away from the four equivalent in-plane <110> directions, giving three-dimensional scattering isosurfaces dominated by structure at the four corners of a square. Spatially resolved reciprocal space mapping using an X-ray beam with dimensions on the order of 1 μm suggests that the four-fold symmetry observed using a larger beam arises from averaging over an ensemble of islands, each with an individual tilt down one direction, rather than from the coexistence of differently tilted domains within a given island.